Eksistensi Alat Musik Tradisional Betep di Desa Sakra Lombok Timur, 2017-2024 - Liana Liana; Abdul Rasyad; Zidni Zidni (Universitas Hamzanwadi, 2024)
This research discusses the existence of the traditional musical instrument Betep in Sakra Village, East Lombok, West Nusa Tenggara. Betep is one of the cultural heritages of the Sasak tribe that is still preserved today, but has not been widely studied academically. The aims of this study are to determine the history of the emergence of the Betep musical instrument, analyze its existence in 2017-2024, and examine people's views on its existence. The method used is qualitative with a historical approach through the stages of heuristics, source criticism, interpretation, and historiography. Data collection was carried out through observation, in-depth interviews with key informants (sekahe figures, community leaders, and religious figures), and documentation. The results show that Betep has existed since ancient times and continues to develop, with a studio built by the youth of Sakra Village in 2017 as a preservation forum. There are ten types of musical instruments in Betep art, namely drums, cemprang, terompong, oncer, gong, perembak, flute, masks, flags, and umbrellas which function as accompaniment to the traditional nyongkolan ceremony. The community views that Betep provides advantages and positive benefits, with the good behavior of sekahe also influencing the sustainability of the studio. This research recommends the need for systematic documentation and revitalization of Betep art for future generations.